Manufatura aditiva por jato de aglutinante (impressão 3D) : fabricação e avaliação de compósitos de gesso com bras de sisal - Coelho, Arthur Wilson Fonseca (2018)
Among the additive manufacturing technologies, 3D printing by binder jetting has a great variety of applications like decorative parts, prototypes, foundry molds, bone implants, and others. This technique needs post-processes to increase the quality of the green parts, and mechanical strength is the most import property. The addition of fibers into the process focus on increasing the strenght is a field with few studies in the Literature. Therefore, this master thesis proposed an incorporation of sisal fibers into the gypsum in the binder jetting process to increase the flexural mechanical strenght of the produced parts. A material characterization was done on raw materials and printed parts by thermogravimetric analysis, X-ray diffraction and scanning electron microscopy. The addition of fibers was studied as a source of variation, and other three factors were considered: printing orientation (length direction and bending direction) and post-process infiltration application. A complete 2 4 factorial design for analysis of variance (ANOVA) was performed to evaluate the contribution of these factors on the mechanical strength and open porosity of the manufactured parts. It was observed that the fibers influenced positively on the mechanical strength of infiltrated parts, but a loss of strength was verified for the green parts. The reason for a loss of mechanical strength was correlated with the increase in porosity caused by the fiber during the printing process, however, this increased porosity contributed to more efficient infiltration post-processing.